Development and evaluation of a generalized ontology framework for software requirement specification - Kundu, Sourav; Das, Soumay Kanti; Md Jamil, Abu Rafe; Islam, Md Kamrul; Kabir, SK. Shalauddin; Akhond, Mostafijur Rahman (Institute of Advanced Engineering and Science, 2025)
This paper presents an ontology developed to address challenges such as com munication gaps, risks of errors, and inconsistencies during the manual process of creating software requirement specifications (SRS). The proposed ontology offers a systematic and formal depiction of the requirements, enhancing consis tency and communication among stakeholders. The ontology has been devel oped from the software requirements documents to facilitate the development process. This paper discusses the process of creating the ontology and demon strates using Pellet Reasoner for inference and Prot´eg´e for ontology construction to save and reuse information. The ontology seems to be efficient in manag ing complex software projects, enabling accurate requirement retrieval through SPARQL queries. This study emphasizes how incorporating ontologies into re quirement engineering can significantly enhance the quality and reliability of SRS.